Ovarian mass in pregnancy: case series - Manvi, M. R.; Deshpande, Radhika (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Ovarian masses in pregnancy are not uncommon. Ovarian masses during pregnancy should be accurately evaluated to identify the patients who need surgical interventions from those where it can be managed conservatively. Ultrasound and magnetic resonance imaging (MRI) are safe diagnostic tools during pregnancy. The overall incidence of ovarian tumours in pregnancy is 2.4-5.7%. Most masses are functional and asymptomatic and up to 70% resolve spontaneously in the second trimester. Both open surgery and laparoscopy can be performed considering the tumour diameter, gestational age and associated complications. A multidisciplinary approach is necessary in case of high suspicion of malignancy. This study evaluates the clinical features, course in pregnancy, management and pregnancy outcome in patients with ovarian masses diagnosed during pregnancy. This was a retrospective analysis of medical records of 6 patients diagnosed with ovarian mass during pregnancy in the department of Obstetrics and Gynaecology at Kanachur Institute of Medical Sciences, Mangalore from June 2019 to June 2020.